Blood, Sweat, and Cheers: Sport and the Making of Modern Canada - Kirby, Sandra (Labour / Le Travail, 2003)
The article reviews the book, "Blood, Sweat, and Cheers: Sport and the Making of Modern Canada," by Colin D. Howell.
Keywords: BLOOD, Sweat & Cheers: Sport & the Making of Modern Canada (Book); BOOKS -- Reviews; HOWELL, Colin D.; Nonfiction; SPORTS -- History